Mothers and other strangers - Haydu, Corey Ann (Little Brown and Company, 2026)
"Two estranged childhood best friends reunite as expectant mothers, after a mysterious falling-out between their own mothers keeps them apart for years?. When Sydney and Mae meet on the playground as toddlers, it seems like kismet. Even their very different mothers--the Type-A Beth Ann and the free-spirited Joni--agree the girls are made for each other, and it's not long before even the mothers become inseparable. Then a falling out draws them apart, and decades later,the loneliness still lingers for the newly pregnant Sydney. Adrift in the absence of her closest friend, Sydney has been drawn into a Multi-Level Marketing scheme, exacerbated by the demands of her inflexible mother, Beth Ann, whose constant scrutiny seems reserved only for her daughter. Across the city, Mae is stunned to find herself single, pregnant, and still haunted by the loss of her mercurial latemother, Joni, whose mysterious death holds as many unanswered questions as Mae does herself. Mae is an artist who has lived under the shadow of the one painting (of two girls) that made her famous yearsago, the success of which confines as much as it defines her. When Sydney and Mae find themselves back in one another's lives, each with a baby girl on the horizon, it once again seems like destiny. Each begins to pull the other away from the coercive influence of outsiders--mommy groups, marketing schemes, artistic pressures, and ex-boyfriends. But the two women will soon discover that it's not destiny that has drawn them together this time, but a devastating secret at the center of their orbits--a truth that finally will bind them or shatter them, for good."--